PENGARUH PEMBERIAN PUPUK KOTORAN SAPI DAN PUPUK TERHADAP PERTUMBUHAN DAN PRODUKSI UBI JALAR (Ipomoea batatas L.) - Jamalludin, Chairil Ezward, Imelda Devega, (Menara Ilmu, 2019)
objective of this research is to information of cow manure and KCL fertilizer that better for sweet potato vegetative and generative growth singly or interaction. The method of the research was Cluster Randomyzed Design (CRD) factorial with two (2) factor. Factor P (Cow manure control, 900gr/plot, 1800gr/plot and 2700gr/plot) factor K (fertilizer KCl control, 2,5gr/plant, 5gr/plant ad 7,5 gr/plant) So there are research consist of 16 combination of parameter, the of experiment 3 replication so any 48 plot. In the plot any 4 plants with 3 plant to sample, so population 192 plants. Parameter of served in the research are : were the ages of shoot appear (day), the total of shoots (shoot), the length of sulur (cm), the weight of umbi (kg). The data analyzed with analysis of variance and followed HSD test 5%. The results showed that the use of cow manure and KCl fertilizer singly and interaction observed significantly and the best result singly cow manure at P3 age of shoot appear 6,22 day, total of shoot 3,03 shoot, length sulur 531,29 cm and weight of umbi 473,33 gr/plot at P2. The best result singly KCl fertilizer at: K3 age of shoot appear 6,25 day, and weight of umbi 504,17gr/plot total of shoot at K2 3,03 shoot, length sulur at K1 515,96 cm. The best result interaction total of shoot P3K3 3,44 shoot, length sulur P3K2 689,00 cm and weight of umbi P3K2 663,33 gr/plot. The combination result of the age of shoot appear not responding. Kay word: sweet potato, Cow manure, fertilizer KCl.